Phylogenetics - Abdurakhmonov, Ibrokhim Y. (IntechOpen, 2017)
Phylogenetics aims to study the evolutionary relatedness of living organisms in our planet. Its application is extended to the key areas such as evolution, classification and taxonomy of living organisms; ecology, diversity, and conservation biology of agrobiocenosis; monitoring of pathogen spread, outbreaks and source of transmissions, forensic analyses, etc. Historically, phylogenetics studies were prevalently based on morphological features of species that helped to classify the 'Tree of Life' on Earth. Modern phylogenetics studies, however, rely more heavily on DNA sequences. In this Phylogenetics book, we aimed to present readers the latest developments in phylogenetics studies that highlight multi-kingdom systems, reticulated evolution and conservation biology of living organisms as well as 'omics'-based phylogenetics advances.